Exploring influencing factors of demand and purchase of plastic and non-plastic materials: a case study of Nigeria - Morolake Bolaji; Motoi Kusadokoro; Atsushi Chitose (World Development Sustainability, 2025)
A major challenge to the use of plastics has been the improper disposal of petrochemical plastics. An emerging economy like Nigeria has experienced a rise in plastic consumption which has not been stabilized thus leading to high plastic waste generation. The aim of the study was to assess factors that influence the reasons for the demand and purchase of plastic and non-plastic materials in Nigeria. This study made use of primary data using 327 respondents. Our findings reveal that the uptake of petrochemical plastics was higher compared to the uptake of paper-based materials and bioplastics. This was majorly due to its available in the Nigerian market. The study further revealed that variables like city, gender, household head gender, age, marital status, household members and number of years of schooling significantly influenced the purchase of plastic and non-plastic materials. Similarly, we discovered that although few respondents purchased bioplastics because they preferred the material type, however most respondents pointed out that income was the most influential factor to the demand for bioplastics. The study concludes that although a few people already have changed their consumption behavior in Nigeria, but for most people, increasing the income is crucial to changing their behavior. The study recommends that pro-growth policies are required to encourage ecofriendly behaviors. The limitation of the study includes the sample size and the high literacy level of respondents. Future research in this area of study should focus on improving the sample size and ensuring inclusivity of all literacy levels.